Agricultural commercialization in the Mekong region: A meta-narrative review and policy implications. Issue 1 (31st December 2023) - Nguyen, Anh-Thu; Oya, Carlos; Beban, Alice; Gironde, Christophe; Cole, Rob; Ehrensperger, Albrecht
ABSTRACT: Agricultural commercialization has been a development focus in the Mekong region for several decades, resulting in varying outcomes. In response to competing claims and policy advice, this meta-narrative review not only examines the literature on the impacts of agricultural commercialization in the Mekong on local livelihoods, but also investigates the research traditions that shape the conceptualization of the research topics, study design, and recommended solutions. We explore narratives from three research traditions, namely the neoclassical, Marxian political economy, and neopopulist approaches. On the whole, the neoclassical literature finds positive impacts on household incomes and thus contributes to reducing poverty; the Marxian political economy tradition finds that capitalist development in agriculture creates and deepens social differentiation through which certain groups may benefit while others are negatively impacted; lastly, the neopopulist perspective finds negative impacts compared to previous, traditional livelihoods. The ideological premises informing these studies and implications for policy are discussed.